Struktur, Dynamik und Bedeutung des antarktischen Wasserringes - Fahrbach, Eberhard; Rohardt, Gerd (2006)
The Southern Ocean: its structure, dynamics and importance: The Antarctic Circumpolar water belt alsocalled the Southern Ocean, plays a significant role in the global climate system. It links the three oceanbasins by means of the Antarctic Circumpolar Current to a global system. The water mass transformationsaround Antarctica are important components of the meridional overturning circulation. Mode and intermediatewater formation are part of a shallow overturning cell, the deep one is driven by deep and bottomwater formation. Zonal and meridonal circulations are dynamically closely linked. The water mass propertiesvary from subtropical to polar conditions. The transitions occur in fronts. Atmosphere ocean sea iceshelf ice interactions control the water mass formation. The oceanic system is subject to significantvariability in a wide range of time scales so that trends can not be detected in the available data.